A Universal Approach to Ultrasmall Magneto‐Fluorescent Nanohybrids1. Issue 42 (2nd July 2015) - Feld, Artur; Merkl, Jan‐Philip; Kloust, Hauke; Flessau, Sandra; Schmidtke, Christian; Wolter, Christopher; Ostermann, Johannes; Kampferbeck, Michael; Eggers, Robin; Mews, Alf; Schotten, Theo; Weller, Horst
Abstract Seeded emulsion polymerization is a powerful universal method to produce ultrasmall multifunctional magnetic nanohybrids. In a two‐step procedure, iron oxide nanocrystals were initially encapsulated in a polystyrene (PS) shell and subsequently used as beads for a controlled assembly of elongated quantum dots/quantum rods (QDQRs). The synthesis of a continuous PS shell allows the whole construct to be fixed and the composition of the nanohybrid to be tuned. The fluorescence of the QDQRs and magnetism of iron oxide were perfectly preserved, as confirmed by single‐particle investigation, fluorescence decay measurements, and relaxometry. Bio‐functionalization of the hybrids was straightforward, involving copolymerization of appropriate affinity ligands as shown by immunoblot analysis. Additionally, the universality of this method was shown by the embedment of a broad scale of NPs.